Factors related to the management of infectious waste from caring for dependent elderly in the community, Maha Sarakham Province, Thailand: 10.55131/jphd/2026/240213 - Dittaphol Jaisue; Nachalida Yukalang; Sumattana Glangkarn (Journal of Public Health and Development, 2026)
This cross-sectional study investigated factors related to the management of infectious waste generated from caring for dependent elderly in community settings. The sample consisted of 429 caregivers of dependent elderly, selected through multi-stage stratified random sampling. Data collection was conducted between October 2023 and February 2024 in 12 sub-district health-promoting hospitals in Maha Sarakham Province. The research instrument was a structured questionnaire comprising five sections including 1) general information about caregivers for dependent elderly, 2) types and quantities of infectious and other waste, 3) knowledge regarding infectious waste management, 4) attitudes toward infectious waste management, and 5) practices in managing infectious waste from caring for dependent elderly. Data were analyzed using descriptive statistics and bivariate analysis, odds ratios and 95% confidence intervals, with statistical significance set at p < 0.05. The response rate was 96.40%. The majority of caregivers were female (86.7%) with an average age of 53.93 years (S.D. = 9.11). Most were married (77.8%) with primary education (50.8%) and an average family income below 18,000 baht (93.0%) (S.D. = 9293.4). Factors significantly associated with infectious waste management from caring for dependent elderly in the community included: caregivers aged 50 years and above (OR 2.162, 95%CI 1.146-4.078), caregivers who received training about elderly care (OR 4.285, 95%CI 1.938-9.476), training about infectious waste management in elderly care (OR 3.211, 95%CI 1.573-6.555), caregivers with good knowledge (OR 2.418, 95% CI 1.227-4.766), and caregivers with positive attitudes toward waste management (OR 2.002, 95%CI 1.008-3.975). Caregivers aged ≥50 years, with training experience, good knowledge, and positive attitudes showed significantly better performance for infectious waste management practices. The findings underscore the urgent need for specialized training programs and evidence-based policy interventions to enhance safety protocols and environmental sustainability in community-based elderly care.